Fig leaves (Ficus carica L.): source of bioactive ingredients for industrial valorization - Shiraishi, Carlos Seiti Hurtado (2022)
The fig tree (Ficus carica L.) was one of the first domesticated trees. In 2019, the world's fig fruit production was estimated at 1153 tons. However, fig leaves are not utilized, resulting in copious quantities of bio-waste. To identify promising fig tree varieties, hydroethanolic extracts were prepared from the leaves of five fig tree varieties (Pasteliere-PA, Longue d'Aout-LA, Dauphinie-DA, Boujassote Noire-BN, and Marseille-MA). The variety with the highest concentration of organic acids was BN (146.5 mg/g dw), while glucose, fructose, and sucrose were the predominant sugars across all varieties. All extracts present alpha-tocopherol as the prevalent tocopherol isoform (above 78%), while PUFA fatty acids were predominant, ranging from 53% to 71% of total fatty acids. BN showed moderate antioxidant activity (EC50 0.23 +/- 0.01 mg/mL), while the DA variety presented promising cytotoxicity against the tumor AGS and MCF-7 cell line (GI(50) 158 +/- 13 and 223 +/- 21 mu g/mL) and especially in the inhibition of Nitric Oxide Production evaluation (IC50 20 +/- 5 mu g/mL). The DA activities are probably related to high concentrations of flavonoids, specifically the predominant apigenin-C-hexoside-C-pentoside and quercetin-O-deoxyhexosyl-hexoside. Finally, the BN and DA varieties showed good antimicrobial activity, especially against Yersinia enterocolitica. Fig leaves can be considered sustainable sources of industrially valuable bioactive molecules, and several potential applications were highlighted.